Regularities of reflecting color characteristic in a inner form of Russian dialectal nominations of medicinal herbs - Kuznetsova, Elena L. (Journal of the Belarusian State University. Philology, 2020)
Russian dialectal phytonyms reflecting color characteristic of herbaceous medicinal plants are considered (one-word motivated names). These names have been classified according the motivation and the nomination character (direct or metaphorical/metonymic). Regularities of reflecting color characteristic of plants in a inner form of such names have been established. It has been determined that one-word names reflecting color characteristic of plants are not numerous in the dialects of the Russian language (in comparison with one-word phytonyms reflecting some of other characteristics of plants). Four types of dialect phytonyms reflecting color characteristic of medicinal herbs have been registered.